2019
DOI: 10.1111/tmi.13334
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the HIV treatment cascade in a South African health sub‐district by gender: retrospective cohort study

Abstract: objectives To quantify the HIV care cascade in a Cape Town sub-district to understand rates of linkage to and engagement in HIV care.methods We used routinely collected data to reconstruct the treatment cascade for 8382 infected individuals who tested HIV + in 2012/2013. We obtained data on patient gender, year of initial HIVpositive test, age at testing and initial CD4 cell count and defined five stages of the HIV care cascade. We quantified attrition across cascade stages.results Two-thirds of the sample (56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 20 publications
(27 reference statements)
0
17
0
Order By: Relevance
“…Follow‐up data for participants were available through the end of 2016. The primary purpose of this original cohort was to examine associations between gender, HIV testing, and subsequent HIV service uptake and outcomes [17]. South Africa has a national death registry; however, data for cohort members were not authorised for linkage to the national death registry.…”
Section: Methodsmentioning
confidence: 99%
“…Follow‐up data for participants were available through the end of 2016. The primary purpose of this original cohort was to examine associations between gender, HIV testing, and subsequent HIV service uptake and outcomes [17]. South Africa has a national death registry; however, data for cohort members were not authorised for linkage to the national death registry.…”
Section: Methodsmentioning
confidence: 99%
“…Notable heterogeneity also exists along the cascade based on participants' reported HIV exposure categories, with MSM progressing relatively well participants reporting IDU having relatively poor odds of reaching virologic suppression. These trends are not unprecedented; similar inequalities across the cascade have been noted in a variety of contexts [28][29][30][31][32]. While our multivariable logistic regression analyses highlight specific inequalities of statistical significance across the cascade, the use of equiplots to analyze disaggregated cascade data is an innovative and important method for identifying inequalities that, although not statistically significant, are highly relevant and should be considered during programmatic planning and design to address population-level inequities in HIV-related health outcomes.…”
Section: Discussionmentioning
confidence: 58%
“…Twenty-eight studies reported on this step [20,23,24,[26][27][28]31,[33][34][35][37][38][39]41,44,45,[47][48][49][50][51][52][53][54][55][56][57][58]: 15 cohort studies, 10 crosssectional and three of mixed design. Twenty-four studies (86%) provided a clear definition of the step (Table 2).…”
Section: Linkage To Pre-art Carementioning
confidence: 99%